The Effect of Current Ratio and Account Receivable Turnover on Return On Assets in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period - Nia Apriyani Pinem; Hasibuan, Thezar Fiqih Hidayat (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aims to determine whether